Comparison of film-coated retarded release pellets manufactured by layering technique or by bed rotor pelletization. (June 2015) - Priese, Florian; Frisch, Toni; Wolf, Bertram
Abstract In order to investigate the influence of coatings for controlled active pharmaceutical ingredient (API) release, two types of pellets were used. Microcrystalline pellets were coated with a model API using the Wurster fluidized bed technique in laboratory scale (layered Cellets). Another type of pellets consisting of microcrystalline cellulose and model API was manufactured by fluidized bed rotor pelletization (matrix pellets (MP)). Both kinds of pellets were coated in a Wurster fluidized bed process with a polymer mixture of ethylcellulose to achieve retarded API release. With layered Cellets and an increased thickness of the ethylcellulose layer, the lag-time was increased and the release rate was decreased. In the case of MP, retardation was less pronounced probable due to inhomogeneous polymer film formation as a result of the porous particle surface. To reduce the surface roughness, the MP were coated with polyvinylpyrrolidone (PVP) as an intermediate smoothing layer, in a first trial step by step. In a second trial, pelletization and the coating steps were performed in an uninterrupted process. Intermediate PVP coating improved the ethylcellulose film formation and led to a more pronounced retardation of API release. The uninterrupted process of matrix pellet manufacturing and coating results in a product with only low retarded release.